ADMINISTRATIVE MEASURES TO SCHOOL SAFETY OF SARABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Jumpadung , Kamonmas; Chawianghong, Bunyanuch; Chulasukhont, Phuwadon (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the administration in accordance with the Safe School Measures of school administrators under the Saraburi Primary Educational Service Area Office 1. 2) compare opinions toward the administration of Safe School Measures among school administrators under the Saraburi Primary Educational Service Area Office 1. classified by their administrative experience and school size. The sample group for the study consists of 300 administrators and teachers from schools under the Saraburi Primary Education Service Area Office 1 for the academic year 2024. The sample size was calculated using the Taro Yamane formula, and stratified random sampling was applied. A questionnaire was used as a tool for data collection, with a reliability coefficient of 0.974. The statistical methods used for data analysis included percentage, mean, standard deviation, one-way ANOVA, and pairwise comparisons using Scheffé’s method. The research results found that; 1) the overall administration of Safe School Measures by school administrators was at a high level in both overall and all individual aspects. When considering each aspect separately, the Cultivation measure received the highest average score, followed by suppression and prevention measures, respectively. (2) Regarding the comparison of opinions on the administration of Safe School Measures, when classified by administrative experience, there was no statistically significant difference overall. However, when classified by school size, a statistically significant difference was found at the .05 level.